Increased risk of incident dementia associated with vitamin D deficiency in glaucoma patients: a TriNetX cohort study - Cheng, Yu-Chen; Lu, Chien-Lin; Wang, Joshua; Tsai, Ming Ling; Lu, Kuo-Cheng (Frontiers in Nutrition, 2026)
IntroductionGlaucoma is a progressive optic neuropathy associated with increased neurodegenerative risk. Vitamin D Deficiency (VDD) is a widespread systemic factor linked to neurobiological dysfunction. This study investigated the longitudinal association between VDD and the 5-year incidence of neurodegenerative outcomes in this glaucoma population.MethodsThis retrospective cohort study used a large electronic health records (EHRs) network. Glaucoma patients were classified as VDD (< 30 ng/mL) or vitamin D adequate (VDA) (≥30 ng/mL). A 1:1 propensity score matching (PSM) procedure matched 10,881 patients per cohort based on 47 covariates. The primary endpoints were the 5-year incidence of unspecified dementia, Alzheimer disease (AD), and Parkinson disease (PD), analyzed using Cox proportional hazards models.ResultsAfter PSM, VDD was associated with a higher 5-year risk of unspecified dementia (HR 1.241, 95% CI 1.066–1.446; p = 0.005), with greater risk in severe deficiency (< 20 ng/mL) (HR 1.493, 95% CI 1.179–1.890; p < 0.001). No association was found between VDD and AD or PD. Major predictors included advanced age (HR 6.84), hypertension (HR 2.70), hypoalbuminemia (HR 2.64), elevated CRP (HR 1.38), and diabetes (HR 1.29). Removing long-term NSAID users reduced the dementia risk to non-significant levels (HR 1.178, 95% CI: 0.998–1.391, p = 0.053), suggesting NSAID anti-inflammatory effects may not counteract VDD-related dementia risk in glaucoma patients.ConclusionVDD is significantly associated with an increased risk of developing dementia in patients with glaucoma. These time-dependent and dose-response findings raise the possibility that correcting vitamin D deficiency may influence neurodegenerative outcomes, additional prospective studies are required to establish causality and clarify clinical implications.